Oriented inner fabrication of bi-layer biomimetic tendon sheath for anti-adhesion and tendon healing - Wei Wang; Jingwen Zhao; Zhixiao Yao; Jiazhi Liu; Zhongmin Shi; Yusheng Li; Jian Zou; Hongjiang Ruan (SAGE Publishing, 2020)
Introduction: Synthetic fibrous membranes unveil a promising field in anti-adhesion of tendons. Meanwhile, oriented nanofiber structures have been widely studied and used in the application of biomedical engineering, particularly in repairing and strengthening effects. Methods: In this study, a bi-layer poly(L-lactic acid) (PLLA) electrospun membrane was fabricated, in which the inner oriented fibrous layer was designed to promote tendon healing while outer random aligned layer was designed to prevent peritendinous adhesion. Results: It was found that fibroblasts were aligned along the oriented fiber of membranes in vitro and in a Leghorn chicken model. In biomechanical tests of repaired tendons, no significant difference was found between oriented fibrous membrane and blank control in maximum tensile strength; both oriented fibrous membranes and random fibrous membranes showed lower work of flexion than blank control, which was consistent with gross assessment. Conclusion: It was practicable to promote tendon healing while preventing adhesion via bi-layer PLLA membranes with an inner-oriented-fiber fabricated structure.